Comparative Analysis of Testicular Histology and lncRNA–mRNA Expression Patterns Between Landes Geese (Anser anser) and Sichuan White Geese (Anser cygnoides) - Ran, Mingxia; Huang, Huaxuan; Hu, Bo; Hu, Shenqiang; Hu, Jiwei; Li, Liang; He, Hua; Liu, Hehe; Wang, Jiwen (Frontiers in Genetics, 2021)
Landes geese and Sichuan White geese are two important genetic materials for commercial goose breeding. However, the differences in the male reproductive capacity between these two breeds and the potential molecular mechanisms and associated key genes have not been reported to date. The present study compared the testicular histology and mRNA–long non-coding RNA (lncRNA) expression patterns to reveal the differences in male reproductive performance between Sichuan White geese and Landes geese, as well as to explore the underlying molecular mechanisms. Histological results showed that the testicular organ index, semen volume, and long diameter of seminiferous tubules of Landes geese were significantly larger than those of Sichuan White geese. Analyses of mRNA-lncRNA expression profile showed that compared with Sichuan White geese, a total of 462 differentially expressed mRNAs (DEGs) (173 up-regulated and 289 down-regulated) and 329 differentially expressed lncRNAs (DE lncRNAs) (280 up-regulated, 49 down-regulated) were identified in Landes geese. Among these DEGs, there were 10 spermatogenesis-related and highly expressed (FPKM > 10) DEGs. Except for SEPP1, all of these DEGs were significantly up-regulated in the testes of Landes geese. Functional enrichment analysis indicated that the pathway related to metabolism progress and phosphoinositol signal is vitally responsible for differences in male reproductive performance between Landes geese and Sichuan White geese. These results show that compared with Sichuan White geese, the spermatogenesis in the testis of Landes geese was more active, which may be mainly related to the inositol phosphate signal. These data contribute to a better understanding of the mechanisms underlying different male reproductive performances between Landes geese and Sichuan White geese. This knowledge might eventually provide a theoretical basis for improving male reproductive performance in geese.